Effectiveness of Investment Management in Makassar City - Zulkifly, Andi; Ibrahim, Muh. Akmal; Sukri, Sukri; Yunus, Muhammad (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Investment management is an effort to save and place funds in a certain period in order to gain profit and increase investment value. This study aims to analyze the effectiveness of investment management in Makassar City. This study uses a qualitative research approach with data collection methods, namely observation, in-depth interviews and documentation. The informants in this study are parties who are authorized and directly involved in investment management in Makassar City. Data sources consist of primary and secondary data. While the data analysis technique used is an interactive analysis model. The results of the study show that the effectiveness of investment management in Makassar City can be said to be quite good. This is evidenced by the increase in investment in Makassar City so that investment targets can be achieved. DPMPTSP as the leading sector also involves and integrates with cross-sectoral government and non-government in an effort to increase investment and optimize digitalization, technology and information in investment services in Makassar City.